2023
DOI: 10.1002/jdn.10277
|View full text |Cite
|
Sign up to set email alerts
|

Administration of agmatine prior to physical or psychological stress in pregnant mice ameliorates behavioural and cognitive deficits in female offspring

Abstract: Physical or psychological stress experienced by a mother during gestation is often associated with serious behavioural and cognitive deficits in newborns. Investigations of protective agents, which could prevent the adverse outcomes of prenatal stress (PS), are warranted. Agmatine is a neurotransmitter putatively involved in the physiological response to stress, and exogenous administration of agmatine has been shown to produce a variety of neuroprotective effects. In this study, we aimed to assess whether pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
2
1
0
Order By: Relevance
“…Considering that several previous studies have indicated that PS might differentially affect each sex (Gué et al., 2004; GhotbiRavandi et al., 2021), the sex‐dependent effects of PS must be taken into account. The findings of our present study are comparable to our recent findings in female offspring (Hassanshahi et al., 2023). Similar to what we observed in the male offspring, PS resulted in impaired locomotor activity, increased anxiety‐like behavior, heightened drug‐seeking behavior, and impaired passive avoidance memory in the female offspring, which were prevented with the administration of agmatine during the pregnancy (Hassanshahi et al., 2023).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Considering that several previous studies have indicated that PS might differentially affect each sex (Gué et al., 2004; GhotbiRavandi et al., 2021), the sex‐dependent effects of PS must be taken into account. The findings of our present study are comparable to our recent findings in female offspring (Hassanshahi et al., 2023). Similar to what we observed in the male offspring, PS resulted in impaired locomotor activity, increased anxiety‐like behavior, heightened drug‐seeking behavior, and impaired passive avoidance memory in the female offspring, which were prevented with the administration of agmatine during the pregnancy (Hassanshahi et al., 2023).…”
Section: Discussionsupporting
confidence: 93%
“…The findings of our present study are comparable to our recent findings in female offspring (Hassanshahi et al., 2023). Similar to what we observed in the male offspring, PS resulted in impaired locomotor activity, increased anxiety‐like behavior, heightened drug‐seeking behavior, and impaired passive avoidance memory in the female offspring, which were prevented with the administration of agmatine during the pregnancy (Hassanshahi et al., 2023). Moreover, our findings indicate that PS had no detrimental effects on hippocampal BDNF both in male and female offsprings.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have indicated that postnatal administration of AGM to pups in the VPA animal model can alleviate ASD‐like symptoms (Kim et al, 2017). Furthermore, scholars have investigated the prenatal application of AGM, revealing that administering AGM to pregnant mice during simulated prenatal stress improves the behavior and cognitive deficits in female offspring (Hassanshahi et al, 2023). However, there is currently no report on the prenatal administration of AGM in the VPA animal model of ASD.…”
Section: Discussionmentioning
confidence: 99%